2019
DOI: 10.1016/s1470-2045(19)30275-x
|View full text |Cite
|
Sign up to set email alerts
|

MRI versus mammography for breast cancer screening in women with familial risk (FaMRIsc): a multicentre, randomised, controlled trial

Abstract: Background: Screening guidelines for women at familial risk of breast cancer without a known causative gene mutation differ internationally. To our knowledge, no randomised controlled MRI-screening trial has been performed. The FaMRIsc-study aims to assess the efficacy of MRI versus mammography screening for familial risk and furthermore assesses the influence of breast density. Methods: In 12 Dutch hospitals, 1355 women aged 30-55 years with a cumulative lifetime risk of ≥20% without a BRCA1/2 mutation were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
84
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(85 citation statements)
references
References 28 publications
(45 reference statements)
0
84
0
1
Order By: Relevance
“…The sensitivity was lower than those of the 50-69 and >70 age groups, with 85% and 80% sensitivity, respectively. 44 High density of breast tissue impairs the sensitivity of mammography, especially in women between 40 and 49 years of age (about 74% of them with high breast density) and 45% of women in their 60s have high breast density 6 Therefore, the immunodiagnostic model could make up the low sensitivity of mammography in young women, especially at high breast density. 2,4,6 Furthermore, the results of this study demonstrated that at stage I of BC, the level of anti-p16 autoantibody was significantly higher than that in stage II, stage III and stage IV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sensitivity was lower than those of the 50-69 and >70 age groups, with 85% and 80% sensitivity, respectively. 44 High density of breast tissue impairs the sensitivity of mammography, especially in women between 40 and 49 years of age (about 74% of them with high breast density) and 45% of women in their 60s have high breast density 6 Therefore, the immunodiagnostic model could make up the low sensitivity of mammography in young women, especially at high breast density. 2,4,6 Furthermore, the results of this study demonstrated that at stage I of BC, the level of anti-p16 autoantibody was significantly higher than that in stage II, stage III and stage IV.…”
Section: Discussionmentioning
confidence: 99%
“…44 High density of breast tissue impairs the sensitivity of mammography, especially in women between 40 and 49 years of age (about 74% of them with high breast density) and 45% of women in their 60s have high breast density 6 Therefore, the immunodiagnostic model could make up the low sensitivity of mammography in young women, especially at high breast density. 2,4,6 Furthermore, the results of this study demonstrated that at stage I of BC, the level of anti-p16 autoantibody was significantly higher than that in stage II, stage III and stage IV. The anti-p16 autoantibody was firstly reported by our group in 2006 45 The p16 protein is a cyclin-dependent kinase inhibitor, and also a negative regulator of the mammalian cell cycle 46 Despite it is not specific for BC, the finding indicates that the anti-p16 antibody could be a biomarker in the early detection of BC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For those women with a positive family history of BC and no mutation in a high/moderate penetrance gene, BC risk can be estimated by predictive models, such as BOADICEA or Tyrer-Cuzyck. In women with a cumulative lifetime BC risk of 25-30%, both annual mammography and breast MRI should be offered (IIB) beginning at the age when their 10-year BC risk reaches 5% (IIIC) [25,26].…”
Section: Management Of Women With Familial Risk and No Germline Mutationmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) has become a cornerstone for the diagnosis of breast cancer (BC) [1][2][3][4]. It has the highest sensitivity of all imaging modalities but is confronted with lacks in speci city [5].…”
Section: Introductionmentioning
confidence: 99%